Oligocene-Miocene foraminifera of the Central Paratethys - Cicha, I.; Rögl, F.; Rupp, C.; Čtyroká, J.; Members of the "Working group on the foraminifera of the Central Paratethys" (Abhandlungen der Senckenbergischen Naturforschenden Gesellschaft, 1998)
Due to the collision of the Indian subcontinent with Asia and the rotation of Africa the Paratethys came into being, an intracontinental sea from the western Alps to inner Asia. This new bioprovince is characterized by its particular geodynamic evolution and specialized aquatic faunas. The Central Paratethys, reaching from Bavaria to the Black Sea, marked by its connections to the Mediterranean, the Indopacific and its occasional total isolation, is shown to be a distinct subprovince deserving an independent stratigraphical concept of regional stages. This atlas is an attempt to present this area of sedimentation and its foraminiferal faunas. 28 scientists of 13 countries have worked on it for several years. The investigated time span includes the Eocene-Oligocene boundary and reaches up to the Middle Miocene (Sarmatian stage). Within the Pannonian stage only a few foraminiferids are known due to the increasing fresh water character of the Pannonian sediments. Within a brief introduction to the regional stratigraphy the correlation with the regional stages of the Eastern Paratethys and the Mediterranean is discussed. Short summaries about the geological development of the various basins of the Central Paratethys were necessary because of their different geodynamic and faunistic evolution. They are complete with range charts of regional stratigraphically important foraminiferal species, which sometimes differ from the compilated range charts of the subsequent atlas. The following areas are discussed: the Alpine Foredeep of Bavaria and Austria, the Carpathian Foredeep from Moravia to the Ukraine and its southern outskirts in NW Bulgaria, the Oligocene to Miocene Flysch sediments within the Carpathians from Moravia to the Ukraine, the basins within the Alpine-Carpathian arch in the Pannonian area and adjacent basins such as the Vienna Basin, the Styrian Basin, the Danube Basin, the South Slovakian Basin, the East Slovakian Basin, the Transcarpathian Basin, the Transylvanian Basin and marginal basins in Serbia, Croatia and Slovenia. The atlas itself presents a selection of about 600 of the most important species, arranged according to the system of LOEBLICH & TAPPAN (1987). Each plate is accompanied by a stratigraphical range chart of the figured species. New genera and species, first discribed within this atlas, are discussed in a systematcal part: Colominellinae POPESCU nov. subfam., Colominella POPESCU nov. gen., Paragaudryinella POPESCU nov. gen., Geminiella POPESCU nov. gen., Porosolenia POPESCU nov. gen., Lapugyina POPESCU nov. gen., Neugeborina POPESCU nov. gen., Gaudryinopsis austriacus RÖGL nov. sp., Planularia karolyi CICHA & RÖGL nov. sp., Lapugyina schmidi POPESCU nov. sp., Uvigerina popescui RÖGL, nov. sp., Svratkina cichai POPESCU nov. sp., Alabamina armellae POPESCU nov. sp., Cassigerinella spinata RÖGL nov. sp. A taxonomical index with original citation, type locality, repository and, in many cases, systematic remarks on the figured species is included. References and a regional and a taxonomical index complete the atlas.